Transparency and the ubiquity of information filtration? - Leaver, Tama; Willson, Michele; Balnaves, Mark (Centre for Culture and Technology, 2012)
In past decades, the notion of information filtering was primarily associated with censorship and repressive, non-democratic countries and regimes. However, in the twenty-first century, filtration has become a widespread and increasingly normalised part of daily life. From email filters—designating some messages important, some less important, and others not worth reading at all (spam)—to social networks—with Facebook and Twitter harnessing social ties to curate, sort and share media—through to the biggest filtering agents, the search engines—whose self-professed aims include sorting, and thus implicitly filtering, all our information—filters are inescapable in a digital culture. However, as filtering becomes ubiquitous and normalised, are citizens en masse becoming too accepting or, worse, largely ignorant, of the power these filters hold?